2023
DOI: 10.1101/2023.01.09.23284342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of inactivated COVID-19 vaccines against SARS-CoV-2 infections among healthcare personnel in Pakistan: a test-negative, case-control study

Abstract: Objective: During the COVID-19 pandemic, several vaccines that were efficacious in randomized controlled trials (RCTs) were authorized for mass vaccination. In developing countries, inactivated vaccines were widely administered. While inactivated vaccines have been deemed effective in reducing disease severity, for healthcare personnel (HCPs), effectiveness against COVID-19 infections is also essential to reduce the risk to vulnerable patients and ensure a stable healthcare workforce. In addition, there are li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…However, we provide valuable clinical evidence regarding the factors associated with disease severity and mortality, specifically in the context of VOC and protective effect of vaccinations. The protective effect observed aligns with the efficacy studies of different vaccines used in Pakistan, which have shown inactivated type of vaccinations were moderately effective against symptomatic COVID-19 20,35.…”
supporting
confidence: 80%
“…However, we provide valuable clinical evidence regarding the factors associated with disease severity and mortality, specifically in the context of VOC and protective effect of vaccinations. The protective effect observed aligns with the efficacy studies of different vaccines used in Pakistan, which have shown inactivated type of vaccinations were moderately effective against symptomatic COVID-19 20,35.…”
supporting
confidence: 80%
“…As the majority of individuals in our cohort had received inactivated vaccines, it is not surprising that most of the breakthrough infections we observed were from participants who received inactivated vaccines. A systematic review and meta-analysis of 28 studies showed that inactivated vaccines reduced ICU admission and death [46] but have low to moderate effectiveness in preventing symptomatic diseases, particularly from emerging SARS-CoV-2 VOC [13] , [47] . However, it is shown that all vaccination types are effective against symptomatic COVID-19 [13] .…”
Section: Discussionmentioning
confidence: 99%